Connaissances du contenu et connaissances technologiques des enseignants en Informatique en milieu francophone - VASSILIS KOMIS; SYLVIANE BACHY; OLIVIER GOLETTI; GABRIEL PARRIAUX; MARYNA RAFALSKA; KONSTANTINOS LAVIDAS (Metaichmio Publications, 2022)
In this article we study the content and technological knowledge of teachers who teach or are preparing to teach computer science in a francophone environment. The research is based on the questionnaire elaborated with the reference to the TPACK model. The content knowledge is studied on the base of the five main domains of computer science (algorithms, languages and programming, machines and networks, data representation, and computer science and society) and the technological knowledge on the base of professional and educational programming languages currently used at school. The study presents a multiple correspondence analysis of the 339 responses that were collected and estimated as valid ones. The findings show that the knowledge declared by the teachers vary. The content knowledge can be grouped in 4 categories (from quite poor and badly structured knowledge to more complete knowledge with stronger links). The technological knowledge falls in two categories depending on the knowledge of professional and educative languages declared by teachers.